Source identification and airborne chemical characterisation of aerosol pollution from long-range transport over Greenland during POLARCAT summer campaign 2008 - Schmale, J.; Schneider, J.; Ancellet, G.; Quennehen, B.; Stohl, A.; Sodemann, H.; Burkhart, J.F.; Hamburger, T.; Arnold, S.R.; Schwarzenboeck, A.; Borrmann, S.; Law, K.S. (Atmospheric Chemistry and Physics, 2011)
We deployed an aerosol mass spectrometer during the POLARCAT (Polar Study using Aircraft, Remote Sensing, Surface Measurements and Models, of Climate, Chemistry, Aerosols, and Transport) summer campaign in Greenland in June/July 2008 on the research aircraft ATR-42. Online size resolved chemical composition data of submicron aerosol were collected up to 7.6 km altitude in the region 60 to 71 N and 40 to 60W. Biomass burning (BB) and fossil fuel combustion (FF) plumes originating from North America, Asia, Siberia and Europe were sampled. Transport pathways of detected plumes included advection below 700 hPa, air mass uplifting in warm conveyor belts, and high altitude transport in the upper troposphere. By means of the Lagrangian particle dispersion model FLEXPART, trace gas analysis of O3 and CO, particle size distributions and aerosol chemical composition 48 pollution events were identified and classified into five chemically distinct categories. Aerosol from North American BB consisted of 22% particulate sulphate, while with increasing anthropogenic and Asian influence aerosol in Asian FF dominated plumes was composed of up to 37% sulphate category mean value. Overall, it was found that the organic matter fraction was larger (85 %) in pollution plumes than for background conditions (71 %). Despite different source regions and emission types the particle oxygen to carbon ratio of all plume classes was around 1 indicating low-volatility highly oxygenated aerosol. The volume size distribution of out-of-plume aerosol showed markedly smaller modes than all other distributions with two Aitken mode diameters of 24 and 43 nm and a geometric standard deviation g of 1.12 and 1.22, respectively, while another very broad mode was found at 490 nm (g =2.35). Nearly pure BB particles from North America exhibited an Aitken mode at 66 nm (g =1.46) and an accumulation mode diameter of 392 nm (g =1.76). An aerosol lifetime, including all processes from emission to detection, in the range between 7 and 11 days was derived ...